2011
DOI: 10.3746/jkfn.2011.40.11.1548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sweet Persimmon Wine on Alcoholic Fatty Livers in Rats

Abstract: Persimmons are shown to contain high levels of phenolics. The present study was designed to investigate if a sweet persimmon wine (SPW) would affect the development of alcoholic fatty liver in rats. Initially, male Sprague-Dawley rats were housed singly in stainless steel wire-bottomed cages in a room of controlled temperature and lighting. The rats had free access to a nutritionally adequate AIN-93G diet and deionized water. After the acclimatization period, rats were weight-matched and assigned to the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…However, there were no significant changes in body weight, organ or tissue weight, or relative liver and epididymal white adipose tissue weight with different experimental treatments except in the M100 group, which showed reduced kidney weight compared to the intact control group. Similar to our study, Nam et al (2011), Bertola et al (2013), and Donepudi et al (2018) reported a weight-losing tendency in animals fed the Lieber-DeCarli ethanol diet. Brien et al (2011) also reported on the effects of sustained ethanol intake on the ethanol oxidation system and ATP production, which led to weight loss.…”
Section: Discussionsupporting
confidence: 91%
“…However, there were no significant changes in body weight, organ or tissue weight, or relative liver and epididymal white adipose tissue weight with different experimental treatments except in the M100 group, which showed reduced kidney weight compared to the intact control group. Similar to our study, Nam et al (2011), Bertola et al (2013), and Donepudi et al (2018) reported a weight-losing tendency in animals fed the Lieber-DeCarli ethanol diet. Brien et al (2011) also reported on the effects of sustained ethanol intake on the ethanol oxidation system and ATP production, which led to weight loss.…”
Section: Discussionsupporting
confidence: 91%
“…Many in vitro and in vivo studies confirmed that fruits such as the mango [ 144 ], grape [ 145 ], blueberry [ 110 ], mulberry [ 146 ], persimmon [ 147 ], pomegranate [ 148 ], cranberry [ 149 ], and wolfberry [ 150 ] play an important role against ALD. This ameliorative effect on ALD was mainly due to the presence of a tangible amount of bioactive compounds in fruits.…”
Section: Multicomponent Food Plant Extracts Against Aldmentioning
confidence: 99%
“…Many other fruits such as apricot [ 162 ], guava [ 163 ], pomegranate [ 148 ], lemon [ 164 ], Citrus depressa [ 165 ], noni fruit [ 166 ], Opuntia ficus indica [ 167 ], jujube [ 168 ], and persimmon [ 147 ] were also reported to mitigate ALD. These findings confirm that daily intake of fruits may be an effective strategy for alleviating ALD.…”
Section: Multicomponent Food Plant Extracts Against Aldmentioning
confidence: 99%